Students' Learning Experience in Constructivist Learning: A Case Study on Islamic Cultural History Subject at Madrasah Aliyah in Pekanbaru - Wendi Saputra; Muh. Wasith Achadi (Edumaspul: Jurnal Pendidikan, 2024)
The learning paradigm that places students as subjects can provide opportunities for them to be physically and mentally active in the learning process. This research aims to analyze students’ learning experience in constructivist learning. This research is important for developing learning methods that align with the needs of contemporary education and enhancing the quality of learning in Madrasah Aliyah. This research employs a qualitative research method using a case study approach. Data collection methods included observation, interviews, and documentation. The collected data underwent analysis involving data reduction, data presentation, and drawing conclusions. The results of this study show that constructivistic learning provides various learning experiences for students, including increased active participation, development of critical thinking skills, making flexible decisions from various perspectives, being involved in designing learning, constructing knowledge, and learning collaboratively. This research puts forward new knowledge about constructivistic learning in the context of SKI subject in Madrasah Aliyah, showing its significance in deepening practical understanding. It makes a valuable contribution to Islamic education literature by offering new perspectives relevant for curriculum development and learning practices. Future research steps could include further evaluation of the effectiveness of constructivistic implementation and its applicability in improving student learning outcomes.